2000
DOI: 10.1001/archinte.160.12.1797
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Cardiorespiratory Symptoms and Increased Physical Activity After Surgically Induced Weight Loss

Abstract: Surgically induced weight loss in patients with severe obesity is associated with a marked relief in symptoms of dyspnea and chest pain and promotes increased leisure-time physical activity. Sleep-disordered breathing may be involved in the pathophysiology of breathlessness and chest discomfort in obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
1
13

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 40 publications
3
119
1
13
Order By: Relevance
“…It has been demonstrated that weight reduction improves functional health, for example, surgically induced weight loss is associated with a marked relief in dyspnea and chest pain. 25,26 However, symptoms like these could also be interpreted as reactions to underlying mental stress, predisposing a life-style causing obesity, and consequently amplify the condition specific problems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that weight reduction improves functional health, for example, surgically induced weight loss is associated with a marked relief in dyspnea and chest pain. 25,26 However, symptoms like these could also be interpreted as reactions to underlying mental stress, predisposing a life-style causing obesity, and consequently amplify the condition specific problems.…”
Section: Discussionmentioning
confidence: 99%
“…With BMI ≥ 40 kg/m 2 (EL A, B, C [14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] 3. BMI criterion may be the current BMI or previously maximum attained BMI of this severity.…”
Section: Indications For Bariatric Surgerymentioning
confidence: 99%
“…The Swedish Obese Subjects (SOS) study with gastric surgery showed a dose-response between weight loss and CVD risk factors, including blood pressure, cholesterol, HDL, uric acid, and blood glucose at 2 years. Lipid benefit required a 30-kg weight loss in this very obese group, although lesser degrees of weight loss benefited the other risk factors (19). In the University Group Diabetes Program (UGDP) study, comparison of placebo with insulin treatment showed no change in mortality, perhaps in part because only the former group showed sustained weight loss.…”
Section: Diagnosis Of Cvdmentioning
confidence: 92%
“…Emoto et al (abstract 554) reported that plasma total homocysteine was associated with ultrasonographic intimal-medial thickness of the carotid and femoral arteries in 81 individuals with type 2 diabetes and 127 healthy control subjects. Hosoi et al (abstract 219) reported that a common mutation in the enzyme methylenetetrahydrofolate reductase, which is involved in the folate-dependent remethylation of homocysteine to methionine, determining plasma homocysteine levels, was associated with an increased level of coronary 19 and 63. Adipose tissue tumor necrosis factor (TNF) mRNA and, to a greater extent, TNF secretion increased with increasing obesity and with increasing insulin resistance, although there was no change in plasma TNF.…”
Section: Cvd Abstractsmentioning
confidence: 99%